Prevalence of Problematic Internet Use and its Association with Psychological Distress and Coping Strategies among Universiti Teknologi Mara Students during the COVID-19 Pandemic - Nikmat, Azlina Wati; Mohd Yusof, Nur Fadhilah; Suddin, Leny Suzana (IIUM Medical Journal Malaysia, 2022)
Introduction: The COVID-19 pandemic is affecting our day-to-day life and brings a serious impact on public mental health. Due to the practice of physical distancing, the Internet technology is being used to accommodate our daily interactions. In view of the increasing dependency towards this technology, its impact on our mental health well-being is indeterminate. This study aimed to examine the association between problematic Internet use, psychological distress, and the type of coping strategies used among Universiti Teknologi MARA students during this pandemic. Materials and Methods: A cross-sectional online survey was conducted using Internet Addiction Test, Kessler Psychological Distress Scale, and Brief Coping Orientation to Problems Experienced (COPE) Inventory. Data was analysed using SPSS version 26. Results: Of the 444 respondents, 32.2% were noted to have problematic Internet use with 61.3% reported psychological distress. Problematic Internet use was associated with higher level of psychological distress (OR = 1.04, 95% CI: 1.01 – 1.08), and the coping strategies of self-distraction (OR = 1.24, 95% CI: 1.04 – 1.47) and behavioural disengagement (OR = 1.29, 95% CI: 1.07 – 1.55). Conclusion: A high prevalence of psychological distress and its association with problematic Internet use and maladaptive coping among students during this pandemic was evident in this study. Hence, the findings from this study could help to provide insight on the state of the psychological well-being of students in higher education institutions as well as to assist the stakeholders in taking measures to help the students dealing with the pandemic.